Effect of Abscisic Acid (ABA) Combined with Two Different Beekeeping Nutritional Strategies to Confront Overwintering: Studies on Honey Bees’ Population Dynamics and Nosemosis - Szawarski, Nicolás (2019)
In temperate climates, beekeeping operations suffer colony losses and colony depopulation of Apis mellifera during overwintering, which are associated with biotic and abiotic stressors that impact bees’ health. In this work, we evaluate the impacts of abscisic acid (ABA) dietary supplementation on honey bee colonies kept in Langstroth hives. The effects of ABA were evaluated in combination with two different beekeeping nutritional strategies to confront overwintering: “honey management” and “syrup management”. Specifically, we evaluated strength parameters of honey bee colonies (adult bee and brood population) and the population dynamics of Nosema (prevalence and intensity) associated with both nutritional systems and ABA supplementation during the whole study (late autumn-winter-early spring). The entire experiment was designed and performed with a local group of beekeepers, “Azahares del sudeste”, who showed interest in answering problems associated with the management of honey bee colonies during the winter. The results indicated that the ABA supplementation had positive effects on the population dynamics of the A. mellifera colonies during overwintering and on the nosemosis at colony level (prevalence) in both nutritional strategies evaluated.